Robert T. Rolf y John K. Gillespie (comps.). Alternative Japanese Drama. Ten Plays. Honolulu: University of Hawaii Press, 1992. 364 pp. - Tanaka, Michiko; Rolf, Robert T.; Gillespie, John K. (Estudios de Asia y África, 1996)
-